2014
DOI: 10.5897/ajb2013.13245
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field in corn grain production and health

Abstract: The effect of electromagnetic field on agricultural characteristics, yield and health conditions of corn hybrids was assessed using biophysical methods, in order to improve production and health of maize grain (Zea mays L.) for human consumption. The seed was exposed to electromagnetic field at an intensity of 480 mT. Hybrids San Juan and San Jose and five times of exposure (3, 6, 9, 12 and 15 min) were evaluated, as well as a (non-irradiated) control, in a completely randomized block design. On average, grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…On the other hand, seeking to contrast this behaviour with others obtained with magnetically treated maize, in the literature it is found that this type of seed has been studied in different varieties for which there was an increase in response to the attack of a pathogen, when the seeds were treated with a electromagnetic field at 60 (Zepeda et al, 2014) length and mass of the root and plant (Aladjadjiyan, 2002;Vashisth & Nagarajan, 2009), vigour indexes (Kataria, Baghel, & Guruprasad, 2015;Vashisth & Nagarajan, 2009;Isaac, Hernández, Domínguez & Cruz, 2011) and establishment (Zepeda et al, 2010). Variables that express effects on germination improvement are reported in: G max between 10% and 16% (Hernandez et al, 2009;Dominguez et al, 2010;Zepeda et al, 2011;Isaac, Hernández, Domínguez,, & Cruz, 2011); V Ger (Dominguez et al, 2010;Shine et al, 2017;Zepeda et al, 2010); MGT and the time to germinate 10%, 25%, and 75% of the seeds have presented significant decrease up to 21% for the MGT (Florez, Carbonell, & Martínez, 2007;Martinez, Florez, & Carbonell, 2017) regarding the control.…”
Section: Plant Materialsmentioning
confidence: 97%
“…On the other hand, seeking to contrast this behaviour with others obtained with magnetically treated maize, in the literature it is found that this type of seed has been studied in different varieties for which there was an increase in response to the attack of a pathogen, when the seeds were treated with a electromagnetic field at 60 (Zepeda et al, 2014) length and mass of the root and plant (Aladjadjiyan, 2002;Vashisth & Nagarajan, 2009), vigour indexes (Kataria, Baghel, & Guruprasad, 2015;Vashisth & Nagarajan, 2009;Isaac, Hernández, Domínguez & Cruz, 2011) and establishment (Zepeda et al, 2010). Variables that express effects on germination improvement are reported in: G max between 10% and 16% (Hernandez et al, 2009;Dominguez et al, 2010;Zepeda et al, 2011;Isaac, Hernández, Domínguez,, & Cruz, 2011); V Ger (Dominguez et al, 2010;Shine et al, 2017;Zepeda et al, 2010); MGT and the time to germinate 10%, 25%, and 75% of the seeds have presented significant decrease up to 21% for the MGT (Florez, Carbonell, & Martínez, 2007;Martinez, Florez, & Carbonell, 2017) regarding the control.…”
Section: Plant Materialsmentioning
confidence: 97%
“…To stimulate seeds prior to sowing, some authors have subjected the seeds of various cash crops to different values of static magnetic fields for different durations [19]. Other authors have repeated the same processes as before but with sinusoidal electromagnetic fields of various frequencies [20]. The presowing stimulation of seeds with a variable electromagnetic field may involve specially designed electromagnets [21].…”
Section: Krylov and Tarakonovamentioning
confidence: 99%
“…В литературных источниках указывается в основном положительный эффект обработки семян магнитным полем на развитие и урожайность кукурузы, подсолнечника, некоторых видов зерновых и овощных культур [5][6][7][8][9][10][11].…”
Section: Introductionunclassified